State enterprise and economic planning in the Irish Republic - Bristow, J. A. (Statistical and Social Inquiry Society of Ireland, 1965)
The establishment of public enterprise in the Republic owes little to ideology, except perhaps before the war when the ideal of national selfsufficiency played some part in the decision to set up such bodies as the Irish Sugar Company In the main, state enterprise has resulted from ad hoc attempts to fill gaps left by private investment, or to resuscitate or reorganise industries which were ineffective but regarded as essential.
Read before the Society, 29 March 1965
Keywords: Economic planning; Irish public sector; State enterprises; 314.15